Poligami dalam Perspektif Gender: Studi Terhadap Kiai di Kabupaten Cirebon - Maliki, Noval; Fitriah, Fitriah; Khoiri, Imam Ali (IAIN Pekalongan, 2019)
This article discusses the concept of gender in polygamy kiai in Cirebon Regency. There are four polygamy kiais who are the resource persons in this study who use qualitative-descriptive methods as this method, with religious education backgrounds that are relatively different each other. Kiai is an important figure for the gender mainstreaming campaign in view of his position which is still considered important in the community. Moreover, gender-biased constructions very often, if not always, hide behind the cloak of religious truth. Their status as polygamy kiai are interesting to study the conception of gender behind them. The results of this study indicate that the views of all polygamy kiai who become the resource persons still have a gender biased construction with religion as the main justification for such views. This indicates that the socialization related to gender equality discourse is still not optimal or at least has obstacles precisely in an environment that has wider religious knowledge.